The Handbook of Speech Perception. - Pisoni, David (Blackwell handbooks in linguistics., 2008)
Speech perception has emerged as a major field of research over the past two decades, as enormous theoretical and technical changes have occurred. The study of speech perception has broadened in scope to encompass and appeal to a wide variety of disciplines including phonetics, auditory and speech science, cognitive science, experimental psychology, computer science, and informatics, among others. The Handbook of Speech Perception is a collection of seminal articles that offer a summary of the technical and theoretical accomplishments in this vital area of research on language processing. The.